Sustainable Human Resource Management Model to Enhance The Performance of Non-Profit Organizations: The Context of Zakat Institutions in Indonesia - Dewi, Meutia; Rosalina, Dhian; Nasution, Yenni Samri Juliati; Marliyah, Marliyah (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to propose a Sustainable Human Resource Management (SHRM) model for Lembaga Amil Zakat (LAZ) in Indonesia, intended to bridge the gap between zakat potential and its realization through the professionalization of amils based on Islamic values and Sharia governance. Drawing upon a systematic literature review (2018–2025), the study synthesizes the indicators, drivers, barriers, and benefits of SHRM. The model emphasizes the reciprocal fit between strategy and HR practices, the integration of economic, social, and environmental sustainability dimensions, and several key enablers: Sharia governance, Islamic work ethics, digital HRM, national HR certification (SKKNI), and Unit Pengumpul Zakat (UPZ) networks. Core practices include mission-based recruitment, key performance indicators (KPIs) that integrate financial performance, social impact, and sharia compliance, certified training programs, proportional and transparent compensation, and structured volunteer management. The phased implementation is designed to enhance competencies, service quality, digital efficiency, and accountability, ultimately leading to increased collection growth, improved distribution accuracy, enhanced HR retention, and increased public trust.